2023
DOI: 10.3389/fpsyt.2023.1158036
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adverse childhood experiences on depression and suicidal behaviors are partially mediated by neuroticism: A subclinical manifestation of major depression

Abstract: IntroductionNeuroticism, a personality trait, can predict major depressive disorder (MDD). The current study aims to determine whether a) neuroticism is a feature of the acute state of MDD, including suicidal behaviors (SB); and b) adverse childhood experiences (ACEs) are associated with neuroticism in MDD.MethodsThis study included 133 participants, 67 healthy controls and 66 MDD patients, and assessed the Big 5 Inventory (BFI), ACEs using the ACE Questionnaire, and the phenome of depression using the Hamilto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…In addition, the findings showed statistically significant differences in the psychological measures, highlighting a disadvantage in the relationships, quality of life, coping strategies, and resilience among those women reporting high levels of neuroticism. Our findings were in line with other works that have provided evidence that neuroticism plays an important role in the onset of depressive symptoms and greatly contributes to individual vulnerability to affective disorders [42,43]. In fact, a wide body of international literature has described neuroticism as a predisposing factor for major depression and anxiety disorders [44], for more stressful experience of life events, and for higher reactivity to the effects of adversity [45].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the findings showed statistically significant differences in the psychological measures, highlighting a disadvantage in the relationships, quality of life, coping strategies, and resilience among those women reporting high levels of neuroticism. Our findings were in line with other works that have provided evidence that neuroticism plays an important role in the onset of depressive symptoms and greatly contributes to individual vulnerability to affective disorders [42,43]. In fact, a wide body of international literature has described neuroticism as a predisposing factor for major depression and anxiety disorders [44], for more stressful experience of life events, and for higher reactivity to the effects of adversity [45].…”
Section: Discussionsupporting
confidence: 92%
“…A Thai translation of the Big Five Inventory (BFI) (John and Srivastava 1999) was utilized to evaluate five personality traits (Luangsurong 2016). The raw scores of the neuroticism dimension were utilized in the current investigation, given its significant contribution to the MDD phenome (Jirakran, Vasupanrajit et al 2023).…”
Section: Methods and Participantsmentioning
confidence: 99%
“…The positive contributors to this principal component encompass symptoms of distress (PSS), anxiety (HADS-A and STAI), depression (HADS-D and TGDS) and neuroticism. Earlier research conducted by Jirakran, Vasupanrajit, Tunvirachaisakul and Maes 23 revealed that one principal component or factor could be extracted from anxiety, depression and neuroticism scores in adults with major depression. Neuroticism has been linked with mood and anxiety symptoms in both clinical 50 and non-clinical [51][52][53] research cohorts, as well as in cross-sectional investigations 54,55 .…”
Section: Presence Of a Dsoa Dimension In Older Adultsmentioning
confidence: 99%
“…The third major finding of this study is that ACE and NLE (especially health and money) have a highly significant impact on the DSOA, and no effects at all on the mCoDy domain scores. ACE and NLE are significant risk factors for depression and other psychological disorders in adulthood 23,24,65 . Kraaij, Arensman and Spinhoven 27 reported that almost all NLE have a small but significant association with depression.…”
Section: Effects Of Aces On the Dsoa And Mcodymentioning
confidence: 99%
See 1 more Smart Citation